Cultivating collaboration: A scoping review of interprofessional learning readiness among medical and other healthcare students - Guardia de Barros, Thales; Menezes, João Daniel De Souza; da Silva , Matheus Querino; dos Santos , Emerson Roberto; Marques e Silva , Raquel Sudária da Cruz; Uyemura , Jessica Rodrigues Roma; Bistafa, Isabela Amaral de Almeida; Rodrigues, Marcos Sanches; Catricala, Thalissa; Costa , Carlos Dario da Silva; Schiavinato, Gustavo; Custódio, Flávia Cristina; et al. (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Interprofessional education is crucial for preparing healthcare professionals for collaborative practice. This scoping review aimed to synthesize available evidence on readiness for interprofessional learning among medical students exposed to interprofessional education during medical school.Methods: Following the JBI methodology for scoping reviews, we searched six databases (PubMed, CINAHL, Scopus, Web of Science, ERIC, and PsycINFO) for studies published between 2017 and 2022. The review process adhered strictly to the JBI guidelines for scoping reviews, including the use of standardized data extraction tools and quality assessment measures. The review process included a consultation phase with key stakeholders. Data were extracted and synthesized using a narrative approach complemented by thematic analysis.Results: Eleven studies met the inclusion criteria. Medical students generally demonstrated moderate to high levels of readiness for interprofessional learning, with variability across years of study. Early exposure to interprofessional experiences positively influenced readiness. Diverse educational interventions, particularly those involving simulation and immersive clinical experiences, effectively enhanced interprofessional learning readiness. Cultural and contextual factors significantly impacted interprofessional attitudes and readiness.Conclusions: This review highlights the importance of integrating interprofessional education experiences throughout medical curricula. The findings suggest that targeted educational interventions can positively influence readiness for interprofessional learning, with potential benefits for future collaborative practice. However, there is a need for more robust, longitudinal studies to strengthen the evidence base and address current limitations in the field.